Three-Year Outcomes of Wet Age-Related Macular Degeneration Treatment in Polish Therapeutic Programs - Małgorzata Figurska; Marek Rękas (Medicina, 2021)
Background and Objectives: Wet age-related macular degeneration (wAMD) is a chronic, progressive disease of the central part of the retina. Standard treatment for wAMD consists of multiple intravitreal injections of anti-vascular endothelial growth factor drugs. The study goal was to evaluate the three-year effectiveness of wAMD treatment with aflibercept and ranibizumab as part of the therapeutic program in routine clinical practice. Materials and Methods: 1430 patients (possessing 1430 wAMD eyes) with median age of 78.0 years (71.0, 83.0) were enrolled in a non-randomized, retrospective, observational, multicenter study; 804 (56.2%) eyes were treatment-naïve. Therapy was carried out in accordance with the guidelines of the treatment program (the fixed or pro re nata regimen). Results: After the first year of treatment, there was a gain of 2.03 (12.15) letters; after the second, 0.94 (13.72) (p ˂ 0.001); and after the third, 0.17 (14.05) (p ˂ 0.001). There was a significant reduction in the central retinal thickness. In the first year, the patients received 7.00 (5.00, 8.00) injections. In the following years, a significantly lower number of injections (4.00 (2.00, 5.00)) was administered. After the first year, there was a significant difference in the distribution of the best corrected visual acuity according to the Early Treatment Diabetic Retinopathy Study protocol, with more frequent values in the ranges > 35 ≤ 70 for this parameter and > 70 letters in the treatment naïve eye subgroup. After the first year, central retinal thickness in treatment-naïve eyes was significantly reduced. Conclusions: Regular treatment of wet age-related macular degeneration as part of the treatment program achieves functional stabilization and significant morphological improvement over a long-term, three-year follow-up, with significantly fewer injections needed after the first year of treatment.